Monitoring the effectiveness of streambank stabilization projects in northeast Kansas - Benitez Nassar, Denisse Maria (Kansas State University, 2019)
Sedimentation of Federal reservoirs in Kansas has been identified as a critical issue affecting municipal and industrial water supplies, flood control, recreation, and aquatic life. Eroding streambanks are major sources of sediment. Many streambank stabilization projects have been installed over the past 20 years, but there has been very little follow-up monitoring of the effectiveness of these practices. The project goal is to quantify the environmental benefits of government-sponsored streambank stabilization and restoration projects in northeastern Kansas, with a focus on six sites in which tree ad rock revetments were installed. Several of the sites had stabilized reaches and similar un-stabilized reaches as controls. Macroinvertebrate bioassessments were conducted at two sites, on the Delaware River and Plum Creek on the Kickapoo reservation, to compare eroding and stabilized stream reaches. Biotic Index, Biological Monitoring Working Party (BMWP), Average Score per Taxon (ASPT), and Elmidae – Plecoptera – Trichoptera (EIPT) were calculated to compare the stabilized sites performance for water quality and aquatic habitat. The biological indices showed habitat quality on stabilized reaches compared to control reaches. Alfa diversity Shannon-Wiener and Simpson indices were calculated and improve in habitat quality and macroinvertebrate diversity was shown in stabilized reaches. Two new cedar revetments were established in 2017 on Little Grasshopper and Wolfley creeks. These cedar revetment installations resulted in heavy sediment deposits after high flow events with the revetments retaining 121 and 48 cubic meters, respectively. A novel method of using exposed roots was used successfully to quantify erosion on Axtell-Schmidt Dairy farm creek and Wolfley creek, where we found an average yearly erosion of 3.39 and 10.26 cm respectively. Other sites also showed reduced erosion on stabilized reaches and a development of vegetation cover along the riparian areas near the streams. Cedar revetments are shown to be a cost-effective stabilization method on smaller streams. Also, these practices and evaluation methods are a good opportunity for community and stakeholder involvement because it is possible to train community members in the monitoring practices. It is recommended to continue monitoring these sites to compare them with the designated control in order to document long-term effects.
Keywords: Streambank; Stabilization; Monitoring; Macroinvertebrates; Dendrogeomophology; Kansas